Structural color for wood coloring: A Review - Jing Hu; Yi Liu; Zhihui Wu (BioResources, 2020)
The color, texture, and natural defects of wood are important factors affecting its commercial value. Change of wood’s surface color is a primary way to improve its value. This study analyzes and summarizes the development status and existing problems of the traditional wood dyeing process and induced discoloration process. It is proposed that color improvement with photonic crystal structure color is a clean and pollution-free ecological biomimetic coloring technology. Its research status in the fields of fiber, fabric, wood, wood-based panel surface color improvement, new coatings for wood, and lignocellulose nanocrystalline structure color film are reviewed. The following aspects were studied: 1) construction and mechanistic study of the wood surface structure color film, 2) light response and interface mechanistic study of the wood surface structure color film, 3) large-scale application technology study of the wood surface biomimetic structure color film, and 4) preparation and functional development of structural color films of lignocellulose nanocrystal.